KEDUDUKAN HUKUM PERJANJIAN SEWA BELI TANAH DAN BANGUNAN DALAM HAL PERALIHAN HAK ATAS TANAH DALAM PUTUSAN MAHKAMAH AGUNG NOMOR.931 K/PDT/2019 - Maharani Harum Puspita Sari; Mia Hadiati (Jurnal Hukum Adigama, 2020)
Land is one of the basic needs of every human being, because humans usually need soil for their activities, and the soil grows through the utilization of natural resources on the surface of the earth. Life exists in most lands, which makes land an important part of human interests, so land is also necessary for the construction of houses as dwellings. Based on Article 28H paragraph (1) of the State Law of the Republic of Indonesia in 1945 (hereby called the 1945 Constitution), it governs that everyone has the right to live prosperously and live in a good and healthy region. The problems in this study can be formulated: How is the legal position of land and building lease agreements in terms of transfer of land rights in supreme court ruling No. 931 K/PDT/2019. Its contents are determined by PT PLN (Persero), employees of PT PLN (Persero) and Public Officials (Notaries), but the agreement made is not balanced between PT PLN (Persero) and its employees because of the difference between PT PLN (Persero) and its employees in the lease agreement that only benefits is PT PLN (Persero). It is best for employees of PT PLN (Persero) to be able to position themselves as buyers rather than employees, this is a better option, because in the eyes of the law buyers and sellers have the same rights.